Femur head osteonecrosis in a patient with sickle cell anemia: Case report (Research, Society and Development, 2023)
Sickle cell anemia (AF) is an autosomal recessive hemoglobinopathy caused by a mutation in chromosome 11 that is observed with the substitution of glutamic acid for valine, leading to the production of hemoglobin variant S (HbS). Osteonecrose is a skeletal complication of AF that commonly occurs in the umber and femur, leading to successive ischemias, due to vaso-occlusion patterns. The diagnosis begins with a history and physical examination aimed at complaints of back pain in the femur region and symptoms of arthralgia during walking, as well as a quadril x-ray. Also, it should be considered in the presence of risk factors such as prolonged use of corticosteroids and alcoholism. The objective of this article is to report a case of diagnostic and therapeutic relevance involving a young woman suffering from FA who evolved with an allergic crisis, with confirmed aseptic osteonecrose in the head of the femur (ONCF). The event begins with high intensity pain crises located in the left quadril, radiating to the femoral region, which causes ambulation. The etiology of the disease is multifactorial, being associated with situations that compromise the blood supply of the femoral head, such as prolonged use of corticosteroids, sequelae and trauma, HIV, blood dyscrasias and, mainly, AF. The existing association between AF and osteonecrose is well established in the literature, however, this complication is still considered rare, being of great relevance to uncover clinical cases that have already occurred, early diagnoses and surgical treatments of ONCF, the quais foram determinants for better outcomes. the table and reinsertion of the patient.